(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the learning psychologists and pedagogists’ views on the metohods of teaching reading primary school pupils. The works by famous scholars, concerning and organizational fundamentals of teaching reading academically giften primary school pupils have been analyzed. The main ways of formation of the rational reading skills (rapid anf analized reading development, assistance in speech development) have been grounded.